MHD boundary layer flow on heat and mass transfer over a stretching sheet with slip effect (Journal of Naval Architecture and Marine Engineering, 2013)
The present paper is to investigate the effect of linear thermal stratification in stable stationary ambient fluid on steady MHD convective flow of a viscous incompressible electrically conducting fluid along a Stretching sheet in the presence of mass transfer and Magnetic effect. The governing equations of continuity, momentum, energy and species are transformed into ordinary differential equations using local similarity transformation. The resulting coupled non-linear ordinary differential equations are solved using Runge-Kutta fourth order method along with shooting technique. The velocity, temperature and concentration distributions are discussed numerically and presented through graphs. The numerical values of skin-friction coefficient, Nusselt number and Sherwood Number at the plate are derived, discussed numerically for various values of physical parameters and presented through Tables.DOI: http://dx.doi.org/10.3329/jname.v10i2.16400